The FhaB/FhaC two-partner secretion system is involved in adhesion of Acinetobacter baumannii AbH12O-A2 strain. Issue 6 (18th August 2017) - Pérez, A.; Merino, M.; Rumbo-Feal, S.; Álvarez-Fraga, L.; Vallejo, J. A.; Beceiro, A.; Ohneck, E. J.; Mateos, J.; Fernández-Puente, P.; Actis, L. A.; Poza, M.; Bou, G.
ABSTRACT: Acinetobacter baumannii is a hospital-acquired pathogen that shows an extraordinary capacity to stay in the hospital environment. Adherence of the bacteria to eukaryotic cells or to abiotic surfaces is the first step for establishing an infection. The A. baumannii strain AbH12O-A2 showed an exceptional ability to adhere to A549 epithelial cells. The AbFhaB/FhaC 2-partner secretion (TPS) system involved in adhesion was discovered after the screening of the recently determined A. baumannii AbH12O-A2 strain genome (CP009534.1). The AbFhaB is a large exoprotein which transport to the bacterial surface is mediated by the AbFhaC protein. In the present study, the role of this TPS system in the AbH12O-A2 adherence phenotype was investigated. The functional inactivation of this 2-partner secretion system was addressed by analyzing the outer membrane vesicles (OMV) proteomic profile from the wild-type strain and its derivative mutant AbH12O-A2ΔfhaC demonstrating that AbFhaB is no longer detected in the absence of AbFhaC. Scanning electron microscopy (SEM) and adhesion experiments demonstrated that inactivation of the AbFhaB/FhaC system significantly decreases bacterial attachment to A549 alveolar epithelial cells. Moreover, it has been demonstrated that this 2-partner secretion system is involved in fibronectin-mediated adherence of the A. baumannii AbH12O-A2 isolate. Finally, we report that the AbFhaB/FhaC system is involved in virulence when tested using invertebrate and vertebrate hosts. These data suggest the potential role that this AbFhaB/FhaC secretion system could play in the pathobiology of A. baumannii .